PENERAPAN MODEL PEMBELAJARAN TIPE JIGSAW LEARNING DALAM MENINGKATKAN HASIL BELAJAR IPS - Rina Ningsih (Metafora: Education, Social Sciences and Humanities Journal, 2020)
Instructor or teacher constitute one of determine factor in understanding to receave succesfull education. Aspecially in the curriculum and increasing SDM that success from trial education. It alwaysrecource to factor the teacher it shows that is famous as actor the teacher in education would. It is also efort studying the student.The teacher was demanded to many effort until be able to create the condition effective studying teaching.In under to teach effective the teacher have to increase aclasion study to the student, and to increase quality teach. The aclasion study student is able to increased the way wraparound the student as active in studying. It means the aclasion to study is very higher and optimal the teacher should seriously while teach the student. Heigher imposible achievement study to created while in creass quality to teach so the teacher able to plan teaching program and able to do in the interaction study teaching.